Doing Business in Kenya 2012 - World Bank; International Finance Corporation (Washington, DC, 2013)
Doing Business in Kenya 2012 is the second subnational report of the Doing Business series in Kenya. In 2009, Doing Business in Kenya 2010 analyzed quantitative indicators on business regulations for 11 cities: Eldoret, Garissa, Isiolo, Kilifi, Kisumu, Malaba, Mombasa, Nairobi, Narok, Nyeri, and Thika. This year, Doing Business in Kenya 2012 documents improvements in the 11 cities previously measured and expands the analysis to 2 new cities: Kakamega and Nakuru. The cities can be compared against each other, and with 183 economies worldwide. Doing Business investigates the regulations that enhance business activity and those that constrain it. Regulations affecting 4 stages of the life of a business are measured at the subnational level in Kenya: starting a business, dealing with construction permits, registering property, and enforcing contracts. These indicators were selected because they cover areas of local jurisdiction or practice. The indicators are used to identify business reforms and the extent to which these have been effective in simplifying the procedures, saving time, and lowering the cost of doing business. The data in Doing Business in Kenya 2012 are current as of March 2012.